Dynamics of West Sumatra NU Fatayat, Three Heroine Nahdliyin Period 1971-1999 - Yola, Nilma; Hakim, Lukmanul (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to explore the role of Fatayat NU West Sumatra during three different leadership periods, namely Khadijah Mawardi, Husna Aziz, and Siti Izzati Aziz. The research method used is the historical method, which includes the stages of heuristics, source criticism, synthesis, and preparation of reports based on the results of data analysis. The results showed that during the leadership of Khadijah Mawardi, Fatayat NU did not show significant movement, especially because at the same time there was monoloyalty to the Golkar Party in the New Order era. Furthermore, during the leadership of Husna Aziz, the role of Fatayat NU began to increase and was recognised by the wider community, especially through cooperation with the Ministry of Religion and UNICEF. However, during the leadership of Siti Izzati Aziz, there was a setback due to her focus on preparing to run as a legislative candidate from one of the political parties at that time.